Pengaruh penggunaan limbah cair pemindangan ikan dalam ransum terhadap lemak daging dan lemak abdominal itik persilangan Mojosari Peking - Shafry Imtiyaz; Luthfi Djauhari Mahfudz; Dwi Sunarti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
This research’s intention was to examined the effect of liquid waste boiled salt fish in the ration on fat and cholesterol meat and abdominal fat percentage of Mojosari Peking crossing duck. The research materials used were 120 of 3 weeks old males Mojosari Peking duck crossing with average initial body weight of 520.30 ± 57.82 g. This experimental design was used completely randomized design (CRD) with 4 treatments and 5 replications with total 20 units experimental each unit consisted of 6 ducks. The treatment used of liquid waste boiled salt fish in rations with level: T0 = 0%, T2 = 2.5%, T3 = 5% dan T4 = 7.5%. The results showed that the the used of liquid waste boiled salt fish have no significant effect (P>0,05) on fat meat, abdominal fat percentage and cholesterol meat. The used of of liquid waste boiled salt fish can be used in the ration up to the level 7.5%.